Teneurin-2 presence in rat and human odontoblasts - Torres-da-Silvali, K. R. [UNESP]; Tessarin, G. W. L. [UNESP]; Dias, C. A. [UNESP]; Guiati, I. Z. [UNESP]; Ervolino, E. [UNESP]; Goncalves, A. [UNESP]; Beneti, I. M. [UNESP]; Lovejoy, D. A.; Casatti, C. A. [UNESP] (Public Library Science, 2017)
Teneurins are transmembrane proteins consisting of four paralogues (Ten-1-4), notably expressed in the central nervous system during development. All teneurins contain a bioactive peptide in their carboxyl terminal named teneurin C-terminal associated peptide (TCAP). The present study analyzed the detailed distribution of teneurin-2-like immunoreactive (Ten-2-LI) cells in developing and mature rat molar teeth, as well as in mature human dental pulps. Ten-2 and TCAP-2 genic expressions were also evaluated in rat and human dental pulps. Finally, Ten-2-LI cells were analyzed during the repair process after dentinpulp complex injury in rat lower molar teeth. For this, histological sections of rat molar teeth and human dental pulps were submitted to immunohistochemical techniques, while total RNA from developing rat teeth and mature human dental pulps were submitted to conventional RT-PCR. Ten-2-LI cells were evident in the initial bell stage of rat molar teeth development, especially in ectomesenchymal cells of the dental papilla. Ten-2-LI odontoblasts showed strong immunoreactivity in rat and human mature teeth. Ten-2 and TCAP-2 genic expressions were confirmed in rat and human dental pulps. Dentin-pulp complex injury resulted in a decrease of Ten-2-LI odontoblasts after traumatic injury. Interestingly, Ten-2-LI cells were also evident in the pulp cell-rich zone in all postoperative days. In conclusion, Ten-2-LI presence in rat and human odontoblasts was demonstrated for the first time and Ten-2/TCAP-2 genic expressions were confirmed in rat and human dental pulps. Furthermore, it was revealed that Ten-2-LI rat odontoblasts can be modulated during the regenerative process.